Alat Pengering Model Rak Bersusun Sistem Kolektor Plat Datar Sumber Energi Panas Matahari Untuk Meningkatkan Mutu Dan Higienis Produk Industri Kecil Kerupuk Dan Jagung Marning Usaha Sima Indah Kupang - Weraman, Pius; Muntasir, Muntasir; Jutomo, Lewi; Harijono, Harijono (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Abstract - Crackers and corn marning flat plate collector systems use solar energy to improve the quality and hygiene of small industrial products crackers and corn marning the Sima Indah brand is a tool that utilizes solar radiation energy after passing through the collecting plate, the heat received is used to dry crackers and corn material marning. The main constituent component of a flat plate collector is the plate as a collector cover, a zinc plate painted black to enhance absorbency to function as an absorber plate, insulating material from cork or wood powder, and blocks and dryers from teak boards. Construction of crackers and corn marning models is very simple because the raw materials and materials for making, workmanship is easy to obtain, the design is short and does not require a long time. The method of community service is the provision of materials, design and manufacture of tools, demonstration of tools and the provision of cracker dryers and marning corn with solar energy flat plate collector systems have been made by a team for small industries Sima Indah corn processed products, simulation tools, special counseling at partner locations and contribute advice as a follow-up in production resilience. The output of the program can increase production value added by 20 kg - 30 kg of raw material to 40 kg - 50 kg, in terms of drying time 4-7 days to 2-3 days and speed in mass production, hygiene and guarantee of cleanliness.